Diversification of Regional Specialty Products: Ladu As Typical Tourist Destinations in Batu City - Rhiza Eka Purwanto; Asrofi Asrofi Asrofi; Gilang Sandhubaya (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2023)
Culinary businesses, especially regional snacks, are being optimized to boost tourist shopping in tourist destinations, one of which is the city of Batu. Batu City actually has typical snacks of the Gunungsari archipelago which are snacks and are known as Ladu. However, the production of Ladu snacks is currently starting to be limited, this is due to the lack of interest of tourists in buying this Ladu product. This research was conducted to find out how the right diversification strategy in increasing and adding variants of Ladu products in order to increase the purchasing power of tourists. The methodology in this study uses qualitative descriptive analysis through observation, interviews and documentation studies. The results of this study show that ladu snacks are produced and distributed by producers to second parties without paying attention to good packaging. The lack of knowledge and development in production makes Ladu snack products less varied both in terms of shape and toppings. This can be seen from the small availability of ladu snacks in several souvenir shops typical of Batu.             The strategy needed to diversify snacks is to use a horizontal concentric type, which is an effort to increase product diversity to increase profitability and achieve higher sales volumes than existing products. Various variants of ladu snacks produced have a sweet and salty taste with chocolate toppings, and cheese. Diversification Strategy is an alternative choice in producing variants of snack products that are of interest to visitors. Thus the visitors will have more choices in determining the choice of taste of ladu snacks.